Gambaran Kadar Vitamin C Pada Minuman Sari Lemon (Citrus limon) Dengan Metode Spektrofotometri UV – VIS Di Kota Samarinda - Lestari, Indriani Novita; Aina, Ganea Qorry; Rica, Fitri Nur (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
Lemon (Citrus limon L.) is more popular in the culinary industry because it has a fresh citrus aroma and parts used with juice. Some of the benefits of lemon can be used as a garnish for food and drinks. One example of a drink made from lemons is lemon juice. The level of vitamin C that the body needs is only around 90 mg, while one lemon (Citrus limon L.) contains 60-100 mg of vitamin C, so one lemon (Citrus limon L.) can meet the body's vitamin C needs (Kristanto, 2013). The purpose of this study was to describe the levels of vitamin C in lemon juice (Citrus limon L.) using UV-Vis spectrophotometry method in Samarinda City. The type of research conducted was descriptive research with random sampling technique. In this study there were 20 samples taken from different traders. The maximum wavelength in the study was 265 nm. The linear regression equation obtained is y=0,0621001x + 0,0132047. The lowest vitamin C levels were found in sample G, which was 18.30 mg/ml and samples with the highest levels of vitamin C were found in sample Q, which was 98.00 mg/ml. There is only 1 (5%) sample that meets the daily intake of vitamin C, namely the Q code sample.